1987
DOI: 10.1007/bf00846657
|View full text |Cite
|
Sign up to set email alerts
|

The prevention of cigarette smoking in children: Two- and three-year follow-up comparisons of four prevention strategies

Abstract: Recent studies have suggested that a prevention program that addresses the social influences that encourage smoking can be effective in deterring cigarette use by adolescents. This study presents 1-, 2-, and 3-year follow-up results from two studies which evaluated three variations of the social influences curriculum and compared them to a health consequences program and a usual-care comparison group. These results suggest that a peer-led, social influences program can restrain smoking among both baseline nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…In eight studies 19, 20, 33, 34, 35, 37, 39, 52, peers of a similar age were nominated by their classmates, while in four studies, older‐age peers were selected by staff or researchers 32, 36, 51, 53. In other programmes, PLs either volunteered 31, 36, 38 or the age or method of selection was unclear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In eight studies 19, 20, 33, 34, 35, 37, 39, 52, peers of a similar age were nominated by their classmates, while in four studies, older‐age peers were selected by staff or researchers 32, 36, 51, 53. In other programmes, PLs either volunteered 31, 36, 38 or the age or method of selection was unclear.…”
Section: Resultsmentioning
confidence: 99%
“…in the past 12 months rather than weekly or monthly) 35; and the effect of including a study which compared peer‐led intervention to teacher‐led intervention 33. In all cases, syntheses gave similar estimates of effect.…”
Section: Tobacco Usementioning
confidence: 95%
See 1 more Smart Citation
“…While the intervention was successful in preventing the onset of experimental smoking in students up to the eighth grade, the program neither decreased smoking levels nor increased the probability of remaining a nonsmoker in students beyond the eighth grade.2 Murray and colleagues3 found that the intervention effects present at the 1-year follow-up of a seventh grade cohort were no longer apparent at the 2-and 3-year follow-ups. [2][3][4][5][6] The most promising approaches to the prevention of tobacco use among adolescents are those that not Telephone calls have often been used to provide interpersonal support for behavioral change, but their use to induce change is relatively untested. A study at the Pawtucket Heart Health Program12 developed an innovative approach both to promote program components and to provide counseling and support by telephone to individuals worldng to reduce their risk of heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…Several higher level variables have been found to be quite influential in their effect on drug use. Availability of drugs (e.g., Joe & Simpson, 1991), drug use legislation (Joksch, 1988), poverty (Murray, Richards, Luepker, & Pallonen 1987), and neighborhood disintegration (Fagan, 1988) are influences at this level associated with drug use. The extraordinary influence of these factors is apparent when these factors can be associated with drug abuse in the existence of benign personality traits and a drug-resistant family environment (Brook, 1993).…”
mentioning
confidence: 99%